ANALISIS STRATEGI PEMASARAN BUAH NAGA (Hylocereus undatus) DI UD SABILA FARM KABUPATEN SLEMAN YOGYAKARTA - Mu'izzah Noor Indriani; Ignatius Suprih Sudrajat; Susi Widiatmi (Fakultas Pertanian UST, 2019)
The demand for fruit commodities always increases every year and it caused in the increase in competition. Each company needs to analyze strategies to develop the business. One of the companies implementing the marketing strategy is UD Sabila Farm. The purpose of this research are 1) to analyze the company's internal and external environment. 2) choose a strategy to implement the company using IFAS and EFAS matrix 3) Analyze the Internal External (IE) matrix on the company. 4) Matching alternative strategies using IE and SWOT matrices. 5) Stage of determining strategy alternatives using QSPM. This research was conducted at UD Sabila Farm in March-April 2019. The method carried out in this study was descriptive analysis and qualitative method approach. Based on the results of the internal condition data with IFE matrix value of Â 3.64 while the EFE matrix value of 3.67 and the QSPM analysis carried out within the company can be implemented as a SO (Strengths-Opportunities) strategy by utilizing all the power to take advantage of the amount with the highest value is 6.45.